2016
DOI: 10.1021/acssynbio.6b00248
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Photoactivatable Genetic Switches Based on the Bacterium Phage T7 RNA Polymerase

Abstract: Genetic switches in which the activity of T7 RNA polymerase (RNAP) is directly regulated by external signals are obtained with an engineering strategy of splitting the protein into fragments and using regulatory domains to modulate their reconstitutions. Robust switchable systems with excellent dark-off/light-on properties are obtained with the light-activatable VVD domain and its variants as regulatory domains. For the best split position found, working switches exploit either the light-induced interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 44 publications
2
70
0
Order By: Relevance
“…30 We worked with these photodimers due to their prevalence in split protein engineering. 6,7,21,24,25,33 We found that Cre, especially when paired with Vvd, showed substantially improved activation relative to Flp when exposed to blue light ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…30 We worked with these photodimers due to their prevalence in split protein engineering. 6,7,21,24,25,33 We found that Cre, especially when paired with Vvd, showed substantially improved activation relative to Flp when exposed to blue light ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 85%
“…At present, the current bacterial optogenetic toolset primarily includes two-component systems 8,19,20 and split proteins. 7,21 Recombinases are proteins that recognize specific 30-50 base pair (bp) sequences of DNA, and excise the "target" DNA between the sites along with one of the recognition sites. Their ability to manipulate DNA makes them particularly useful for complex cellular logic circuits and engineering gene circuits with memory.…”
Section: Introductionmentioning
confidence: 99%
“…[285][286][287][288]). These include mRNA stability [289,290], codon usage [291][292][293][294], riboswitches [12,295], ribosome binding site potency [296,297] and even the RNA polymerase itself [298] (including photoswitchable variants [299]). …”
Section: Control Factor Expression Engineeringmentioning
confidence: 99%
“…Other split photoactivatable enzymes, such as Cas9 [34] and T7 RNA polymerase [35], have been developed using similar approaches. It should be noted that all split systems have a certain level of background activity, due to the intermolecular interaction between the two protein fragments and/or dark interaction between photodimerizers.…”
Section: Reconstitution Of Split Proteinsmentioning
confidence: 99%
“…In many cases, dark background can be reduced by optimizing the binding affinity of photodimerizers or protein expression level [32,33]. Furthermore, other engineering strategies, such as allosteric regulation [35] and subcellular localization [36], can be combined with protein splitting to reduce background in optogenetic systems.…”
Section: Reconstitution Of Split Proteinsmentioning
confidence: 99%